Analysis of Slang Words in the Lyrics of Coldplay’s Songs on the Album “X&Y”: A Semantics Study - Evita Nasution; Ervina C M Simatupang (Jurnal Sinestesia, 2023)
The aims of this research are to analyse, identify and classify the words that use slang words of Coldplay’s songs. The purpose of this research is to analyze the types of slang by using song lyrics of Coldplay’s songs. The research uses descriptive qualitative method. The theory of Patridge (2004:204) and Leech theory (1981) are used in this research. The data were collected by listening to 5 songs by Coldplay and reading the lyrics of the songs. The result of this research shows that there are six types of slang words in Coldplay’s songs which is with 16 data consisting of Cockney slang, Workmen's slang, Art slang, Church slang, Soldier slang, and Primary slang, namely "Wanna" which is short for the word "Want to". The results of this research also shows that there are Five meanings of slang in Coldplay’s songs namely, Conceptual meaning, Connotative meaning, Affective meaning, Reflective meaning, and Thematic meaning. Stylistic meaning and Collocative meaning were not found.